Vol. 35 : Research Paradigms Transformation in Social Sciences (RPTSS 2017): International Conference, 18-21 May 2017, Tomsk, Russia; [proceedings]; The European Proceedings of Social & Behavioural Sciences (EpSBS) - Ardashkin I. B. Igor Borisovich (2018, 2018)
Title screen